"Catalogus clarorum Hispaniae scriptorum" Waleriusza Andrei jako źródło informacji o recepcji literatury antycznej - Witczak, Agnieszka (Collectanea Philologica, 2024)
Valerius Andrea’s work Catalogus clarorum Hispaniae scriptorum contains the names of all Spanish authors whose works Valerius managed to find in German libraries. This catalog is therefore a valuable source not only for learning about authors writing in Latin, but also for learning about the fate of Latin literature from antiquity to the 17th century, at the beginning of which this work was written.